Rancang Bangun Alat Ukur Kadar Air dan Keasaman untuk Mengetahui Kualitas Madu Berbasis Mikrokontroler - Saputra, Taufik; Firmawati, Nini (Jurnal Fisika Unand, 2024)
Honey is a naturally sweet substance produced by honeybees from the nectar of flowers. The composition of honey is so complex that the benefits of honey in the pharmaceutical, food, beverage and aesthetic industries are enormous. One of the quality parameters of honey is the level of moisture and acidity. This research aims to analyse the quality of honey based on moisture content and acidity. To test this, a tool is needed that can detect moisture content and acidity in honey. The design of a tool to measure moisture content and acidity to determine the quality of honey using capacitive soil moisture sensor and pH sensor has been made. The testing of the tool is done with 3 variations of honey samples available in the market. The test results of 3 honey samples with the designed tool were compared with the pH meter and Brix refractometer. The percentage error obtained in testing the designed tool is 12.5% for moisture content and 3.89% for acidity. Based on the research results, it is found that the designed tool can read the value of water content and acidity in each honey sample.